2017
DOI: 10.1186/s40885-017-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of uncontrolled hypertension among clients on anti-retroviral therapy in Kadoma City, Zimbabwe, 2016

Abstract: BackgroundClients on anti-retroviral therapy (ART) are living longer and have risk of hypertension. Side effects of medicines and aging increase this risk. Hypertension prevalence among clients on ART in Kadoma City was estimated to be 30% in 2015. Of these, 61% had uncontrolled hypertension. This was high compared to 46% of hypertensives in the general population who had uncontrolled hypertension. We determined factors associated with uncontrolled hypertension among clients on ART.MethodsA 1.1 unmatched case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
4
2
Order By: Relevance
“…In the current study, the overall prevalence of uncontrolled hypertension was 56.83%. In comparison to other studies conducted in Africa, the figure presented in this study was slightly lower than those reported in Zimbabwe (61.0%) [25] and Nigeria (60.0%) [26], but higher than the 52.7% reported in Ethiopia [27]. In comparison to other studies conducted in different parts of South Africa, the result is lower than the 75.5% that was reported in the rural Eastern Cape province [12]; however, it is higher than the 13.5% prevalence that was reported in the South African National Health and Nutrition Examination Survey [14].…”
Section: Discussioncontrasting
confidence: 97%
“…In the current study, the overall prevalence of uncontrolled hypertension was 56.83%. In comparison to other studies conducted in Africa, the figure presented in this study was slightly lower than those reported in Zimbabwe (61.0%) [25] and Nigeria (60.0%) [26], but higher than the 52.7% reported in Ethiopia [27]. In comparison to other studies conducted in different parts of South Africa, the result is lower than the 75.5% that was reported in the rural Eastern Cape province [12]; however, it is higher than the 13.5% prevalence that was reported in the South African National Health and Nutrition Examination Survey [14].…”
Section: Discussioncontrasting
confidence: 97%
“…In the current study, the overall prevalence of uncontrolled hypertension was 56.83%. In comparison to other studies conducted in Africa, the figure presented in this study was slightly lower than those reported in Zimbabwe (61.0%) [25] and Nigeria (60.0%) [26], but higher than the 52.7% reported in Ethiopia [27]. In comparison to other studies conducted in different parts of South Africa, the result is lower than the 75.5% that was reported in the rural Eastern Cape province [12]; however, higher than the 13.5% prevalence that was reported in the South African National Health and Nutrition Examination Survey [14].…”
Section: Discussioncontrasting
confidence: 97%
“…Moreover, an increase in the frequency of cardiovascular disease in people with aids has been observed, especially hypertension, which is characterized by systolic blood pressure greater than or equal to 140 mmHg and diastolic blood pressure greater than or equal to 90 mmHg 3 - 4 . However, it is not known whether this is related to increases in the patients’ survival rate, whom now reach older ages; if it is related to the HIV infection itself; if it can be assigned to ART as a result of adverse drug events; or, if all of these factors contribute synergistically to the occurrence of cardiovascular diseases 2 - 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also show that many people with aids have unhealthy lifestyles regarding their feeding, exercise, alcohol consumption and smoking habits, in addition to traditional hypertension risk factors, which include advanced age, male gender, African ascent, high body mass index (BMI) and high cholesterol 3 , 6 . Thus, efforts to reduce cardiovascular risk in patients using ART should focus on prevention and control of hypertension, because this is a common, known and modifiable predictive factor 3 - 4 .…”
Section: Introductionmentioning
confidence: 99%